'Good enough' access: digital inclusion, social stratification, and the reinforcement of class in the Philippines. Issue 2 (3rd April 2019) - Uy-Tioco, Cecilia S.
ABSTRACT: Digital inclusion should be understood in ways beyond access and must take into consideration class formation, the stratification of information, and structural systems of power. Although Philippine telecoms have continually developed products and services for the working poor, the question of what kinds of access persists. This article examines the different ways Filipinos are able to be digitally connected through prepaid mobiles, inexpensive internet access such as Pisonet, and as labourers in information technology-business process outsourcing (IT-BPO) companies. I argue that what is taking place is a 'good enough' access that reinforces existing class structures and raises new questions regarding inclusion. While there are increasingly new ways for Filipinos to be connected, digital inclusion also reveals new forms of social stratification, not simply between the 'haves' and 'have nots' but rather, from the uneven access that is dictated by one's accumulation of economic and cultural capital.